Interpretacje sceniczne rosyjskiej dramaturgii pierwszego trzydziestolecia XX wieku na scenach polskich (Tango Oberiu 1928. Rewia pure nonsense z ponurym zakończeniem) - Gracla, Jadwiga (Acta Polono-Ruthenica, 2018)
The paper is the attempt to compare the text of Daniil Kharms Yelisaveta Bam and her free theatrical production made in Rozrywka Theatre by Łukasz Czaja. The author considers similarities of the text and scenography, reflecting not only Charms’ assumptions but also producer’s stage concepts of The Great Reform of the Theater. The author also points out differences making a show out of Charms’ performance, closer to modern viewer, however, leveling the signs and atmosphere of the times when Charms’ drama was created